1 ML Wetting Layer upon Ga(As)Sb Quantum Dot (QD) Formation on GaAs Substrate Monitored with Reflectance Anisotropy Spectroscopy (RAS). (14th November 2018) - Fouckhardt, Henning; Strassner, Johannes; Loeber, Thomas H.; Doering, Christoph
Abstract : III/V semiconductor quantum dots (QD) are in the focus of optoelectronics research for about 25 years now. Most of the work has been done on InAs QD on GaAs substrate. But, e.g., Ga(As)Sb (antimonide) QD on GaAs substrate/buffer have also gained attention for the last 12 years. There is a scientific dispute on whether there is a wetting layer before antimonide QD formation, as commonly expected for Stransky-Krastanov growth, or not. Usually ex situ photoluminescence (PL) and atomic force microscope (AFM) measurements are performed to resolve similar issues. In this contribution, we show that reflectance anisotropy/difference spectroscopy (RAS/RDS) can be used for the same purpose as an in situ, real-time monitoring technique. It can be employed not only to identify QD growth via a distinct RAS spectrum, but also to get information on the existence of a wetting layer and its thickness. The data suggest that for antimonide QD growth the wetting layer has a thickness of 1 ML (one monolayer) only.